Mechanisms Underlying Host-Microbiome Interactions in Pathophysiology of Human Diseases (Physiology in Health and Disease,, 2018)
Only recently have we begun to appreciate the role of microbiome in health and disease. Environmental factors and change of life style including diet significantly shape human microbiome that in turn appears to modify gut barrier function affecting nutrient & electrolyte absorption and inflammation. Approaches that can reverse the gut dysbiosis represent as reasonable and novel strategies for restoring the balance between host and microbes. In the book, we offer summary and discussion on the advances in understanding of pathophysiological mechanisms of microbial host interactions in human diseases. We will not only discuss intestinal bacterial community, but also viruses, fungi and oral microbiome. Microbiome studies will facilitate diagnosis, functional studies, drug development and personalized medicine. Thus, this book will further highlight the microbiome in the context of health and disease, focusing on mechanistic concepts that underlie the complex relationships between host and microbes.